CD150-mediated Akt signalling pathway in normal and malignant B cells - Yurchenko, M.; Shlapatska, L.M.; Romanets, O.L.; Ganshevskiy, D.; Kashuba, E.; Zamoshnikova, A.; Ushenin, Yu.V.; Snopok, B.A.; Sidorenko, S.P. (Experimental Oncology, 2011)
Aim of this article is to study upstream and downstream events in CD150-mediated Akt signaling pathway in normal human B cells, EBV-transformed lymphoblastoid (LCL) and malignant Hodgkin’s lymphoma (HL) B cell lines.